Effect of Whole-body [18F]Fluoro-2-deoxy-2-d-glucose Positron Emission Tomography in Patients with Suspected Brain Metastasis - Ora, Manish; Soni, Neetu; Nazar, Aftab Hasan; Mehrotra, Anant; Mishra, Prabhakar; Gambhir, Sanjay (Indian Journal of Neurosurgery, 2022)
Background and Purpose [18F]Fluoro-2-deoxy-2-d-glucose (FDG) positron emission tomography/computed tomography (PET/CT) has a promising role in the workup and management of carcinoma of unknown primary (CUP). We have evaluated the effect of whole-body FDG PET/CT in assessing the patients presented with suspected brain metastasis (CUP-BM) on brain magnetic resonance imaging (MRI) or computed tomography (CT).Materials and Methods This retrospective study included FDG PET/CT of 50 patients (24 males, mean: 58 ± 12.2 years old) with a CUP-BM diagnosis based on MRI and CT imaging. The final diagnosis of primary brain neoplasm (BP) or brain metastases (BM) was based on FDG PET/CT findings and/or histopathology (HPE).Results On FDG PET/CT, 52% (26/50) of patients did not have any systemic lesion apart from a brain lesion. Out of these, 50% (13/26) had HPE confirmation of primary brain neoplasm (BP). FDG PET/CT identified multiple systemic lesions apart from brain lesions in the remaining 48% (24/50) of patients. They were categorized as the brain metastases (BM) group. The primary lesions were located in the lungs (n = 20), kidneys (n = 1), prostate (n = 1), esophagus (n = 1), and tongue (n = 1).Conclusion FDG PET/CT could suggest a diagnosis of BM based on the presence of systemic lesions. It also provides an easily accessible peripheral site for biopsy and systemic disease burden in a single scan. FDG PET/CT's up-front use in suspected CUP-BM on CT and/or MRI could differentiate the BM from BP in most cases and avoid brain biopsy in the BM group.
Keywords: FDG PET/CT; brain metastases; carcinoma of unknown primary